The functional triangle of the structural units "author – performer – viewer" (based on the material of play "The four projects of the Ukrainian national flag" by Yuriy Tarnavskiy) - Шовкопляс, Галина Євгенівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article reviews the structural principles of the experimental play by Tarnavskiy "The four projects of the Ukrainian national flag". The play itself, in the opinion of researchers, is close to the performance format. The article analyzes the influence of Jerzy Grotowski's theory, better known as Jerzy Grotowski's The Poor theater, on the dramaturgy of Yuriy Tarnavskiy. A separate analysis is dedicated to the article "Text and theater", which should be considered a cornerstone of Tarnavskiy's dramaturgy: this article specifically outlines Tarnavskiy's principal foundations in regards to modernism.